24-hour time-dependent aspirin efficacy in patients with stable coronary artery disease - Henry, Patrick; Vermillet, Adeline; Boval, Bernadette; Guyetand, Carine; Petroni, Thibaut; Dillinger, Jean-Guillaume; Sideris, Georgios; Sollier, Claire Bal dit; Drouet, Ludovic (Thrombosis and Haemostasis, 2011)
Aspirin-induced cyclooxygenase (COX)-1 acetylation is irreversible and it is assumed that the platelet thromboxane-A2 aggregation pathway is inhibited for at least 24 hours (h) after aspirin ingestion. However, time course of biological efficacy of daily low-dose aspirin has rarely been assessed in patients with coronary artery disease (CAD). We aimed to assess the 24-h biological efficacy of daily low-dose aspirin in CAD patients. The peak and trough (2 h –24 h) effect of a chronic treatment with once daily dose aspirin were studied in 150 consecutive stable CAD patients. The main outcome measure was light transmission aggregometry (LTA) triggered with 0.5 mg/ml arachidonic acid (AA). In the last 47 consecutive patients, additional tests were conducted at 6, 12, 16, 20 h after last aspirin administration. 4.7% of the patients had significant aggregation (>20% maximal intensity LTA-AA) 2 h after aspirin ingestion and 24.7% at 24 h (p<0.0001). The more precise assessments in the last 47 patients showed that significant platelet aggregation progressively reappeared with time after aspirin intake (2 h – 4% of patients, 6 h – 4%, 12 h – 11%, 16 h – 16%, 20 h – 19% and 24 h – 28%). Concordant results were observed using production of thromboxane-B2 and other techniques evaluating AA-induced platelet aggregation/activation. No significant differences were found between lower (75–100 mg/day) and higher (>100 mg/day) dose aspirin. Such aspirin «resistance» at 24 h after ingestion was related to biological inflammatory markers, current smoking and diabetes. In conclusion, once daily aspirin does not provide stable 24-h antiplatelet protection in a significant proportion of CAD patients. Any biological assessment of aspirin efficacy should take time since last aspirin intake into consideration.
Keywords: Platelet aggregation; aspirin; aspirin resistance; coronary artery disease